2018
DOI: 10.1155/2018/1764212
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Chicory on Serum Uric Acid, Renal Function, and GLUT9 Expression in Hyperuricaemic Rats with Renal Injury and In Vitro Verification with Cells

Abstract: Hyperuricaemia (HUA) is an independent risk factor for chronic kidney disease. Urate crystals are deposited in the kidney and can cause renal tubular interstitial fibrosis, leading to renal dysfunction. Chicory extract (hereafter referred to as chicory) clearly reduced serum uric acid levels in rats with HUA induced by 10% fructose. This is the first study to observe the effect of chicory on serum uric acid levels and renal function in rats with HUA and renal injury. In vivo studies using hyperuricaemic rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…C. intybus L., commonly known as chicory, is often used as a cholagogic and diuretic agent, which conforms to the therapeutic principle of hyperuricemia and gout in Chinese traditional medicine. Our previous studies demonstrated the promising effect of chicory on lowering serum urate levels [22,23,24,25], and other reports have also shown the anti-inflammatory effect of chicory extract [26]. Combining the traditional use of and modern pharmacological research on chicory, we posited that chicory may be a safe antigout agent that can address both the symptoms and root causes of gout.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…C. intybus L., commonly known as chicory, is often used as a cholagogic and diuretic agent, which conforms to the therapeutic principle of hyperuricemia and gout in Chinese traditional medicine. Our previous studies demonstrated the promising effect of chicory on lowering serum urate levels [22,23,24,25], and other reports have also shown the anti-inflammatory effect of chicory extract [26]. Combining the traditional use of and modern pharmacological research on chicory, we posited that chicory may be a safe antigout agent that can address both the symptoms and root causes of gout.…”
Section: Discussionmentioning
confidence: 86%
“…Moreover, the Food and Drug Administration (FDA) has classified chicory extract as “generally regarded as safe” and listed it in the “Everything Added to Food in the United States” category [21]. In previous studies, we found that chicory could significantly decrease serum uric acid, and its anti-hyperuricemia effect may be associated with both the inhibition of urate formation by suppressing xanthine oxidase activity and the promotion of urate excretion by regulating transporter expression [22,23,24,25]. The literature also shows that chicory possesses anti-inflammatory activity [26].…”
Section: Introductionmentioning
confidence: 99%
“…The nephroprotective effect of the extract was confirmed in the human kidney cell line through inhibition of GLUT-9 expression, an important transporter of uric acid in kidneys. Chicory extract could also decrease renal damage in an experimental model of chronic renal failure; however, the administered doses of the extract (6.6 and 13.2 g/ kg) were dramatically higher than benzbromarone (20 mg/kg) as the standard drug (Jin et al, 2018).…”
Section: Chicory (Cichorium Intybus L)mentioning
confidence: 93%
“…We focused our attention particularly on systematic reviews and meta-analysis, when possible, or on single in vitro, in vivo, and clinical trials studies, applying no time filters. Based on this data, specific and detailed tables were produced ( Table 4 and Supplementary Materials Table S1 [ 2 , 3 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , ...…”
Section: Methodsmentioning
confidence: 99%